2023
DOI: 10.1001/jamaoncol.2022.6288
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and Predictive Value of Immune-Related Gene Expression Signatures vs Tumor-Infiltrating Lymphocytes in Early-Stage ERBB2/HER2-Positive Breast Cancer

Abstract: ImportanceBoth tumor-infiltrating lymphocytes (TILs) assessment and immune-related gene expression signatures by RNA profiling predict higher pathologic complete response (pCR) and improved event-free survival (EFS) in patients with early-stage ERBB2/HER2-positive breast cancer. However, whether these 2 measures of immune activation provide similar or additive prognostic value is not known.ObjectiveTo examine the prognostic ability of TILs and immune-related gene expression signatures, alone and in combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 51 publications
2
19
0
Order By: Relevance
“…93 progression-free survival. 95 Researchers suggest that ERBB2 type 1 T-helper cell counts in peripheral blood can be used to forecast positive clinical outcomes following trastuzumab therapy. 96 The results of this phase 1 nonrandomized clinical trial indicate that the ERBB2 ICD vaccine was linked to the induction of immunity at all dosages, with the highest levels of immunogenicity being at 100 and 500 μg.…”
Section: Dna-based Vaccine For Tnbcmentioning
confidence: 99%
See 1 more Smart Citation
“…93 progression-free survival. 95 Researchers suggest that ERBB2 type 1 T-helper cell counts in peripheral blood can be used to forecast positive clinical outcomes following trastuzumab therapy. 96 The results of this phase 1 nonrandomized clinical trial indicate that the ERBB2 ICD vaccine was linked to the induction of immunity at all dosages, with the highest levels of immunogenicity being at 100 and 500 μg.…”
Section: Dna-based Vaccine For Tnbcmentioning
confidence: 99%
“…When paired with anti‐PD‐L1 checkpoint blockade immunotherapy, E0771, and 4T1.2‐specific polyepitope neoantigen DNA vaccines were able to elicit strong immune responses and suppress tumor growth. Following trastuzumab administration, patients with breast cancer who develop ERBB2 (formerly HER2)‐specific immunity—specifically, responses that target the protein's ICD—are more likely to experience favorable clinical outcomes, such as OS and progression‐free survival 95 . Researchers suggest that ERBB2 type 1 T‐helper cell counts in peripheral blood can be used to forecast positive clinical outcomes following trastuzumab therapy 96 .…”
Section: Dna‐based Vaccine For Tnbcmentioning
confidence: 99%
“…We hypothesized that the biological tumor and immune heterogeneity of ERBB2/HER2 -positive EBC contribute to the inconsistent results coming from different neoadjuvant and adjuvant clinical trials. In this analysis, we examined how intrinsic subtype, immune activation status, and other gene expression signatures contribute to pCR and EFS, and the benefit of dual therapy with trastuzumab and lapatinib compared with single-agent trastuzumab, by performing individual patient-level biomarker analysis of 3 phase 3 clinical trials with similar designs: NeoALTTO, CALGB 40601, and NSABP B-41 …”
Section: Introductionmentioning
confidence: 99%
“…Activation of the immune system, as measured by the expression of TILs and/or immune-related gene expression (iGES) signatures, has been intensely investigated as a potential biomarker in the neoadjuvant setting. While the expression of TILs in HER2+ BC has consistently correlated with poor prognostic features such as estrogen receptor (ER)-negativity (37)(38)(39) and high histological grade (39), it has at the same time correlated with higher pCR rates (37,38,(40)(41)(42) and, in some (38,41) but not all studies (35,39), with improved cancer outcomes. However, in some studies, TILs were shown potentially inferior to some iGES in predicting pCR in both HER2+ (37,42) and triple negative breast cancer (TNBC) (43).…”
mentioning
confidence: 99%
“…While the expression of TILs in HER2+ BC has consistently correlated with poor prognostic features such as estrogen receptor (ER)-negativity (37)(38)(39) and high histological grade (39), it has at the same time correlated with higher pCR rates (37,38,(40)(41)(42) and, in some (38,41) but not all studies (35,39), with improved cancer outcomes. However, in some studies, TILs were shown potentially inferior to some iGES in predicting pCR in both HER2+ (37,42) and triple negative breast cancer (TNBC) (43). Furthermore, as with Ki-67 (44) measurements are tricky to standardize (38,(45)(46)(47); hence the special interest in digital assessments-in addition to its potential cost-saving and wider applicability in places where restricted access to specialist pathologists is the rule.…”
mentioning
confidence: 99%